2019
DOI: 10.1038/s41612-019-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of orography on large-scale atmospheric circulation

Abstract: Some of the largest and most persistent circulation errors in global numerical weather prediction and climate models are attributable to the inadequate representation of the impacts of orography on the atmospheric flow. Existing parametrization approaches attempting to account for unresolved orographic processes, such as turbulent form drag, low-level flow blocking or mountain waves, have been successful to some extent. They capture the basic impacts of the unresolved orography on atmospheric circulation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 76 publications
(78 reference statements)
8
76
0
Order By: Relevance
“…Recent study by Sandu et al. () suggests that parameterization schemes on topographic processes (e.g., turbulent form drag, low‐level flow blocking, and mountain waves) may also impact on the atmospheric circulation. Optimizing the parameterization schemes could be helpful for further improving the RWS simulation.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study by Sandu et al. () suggests that parameterization schemes on topographic processes (e.g., turbulent form drag, low‐level flow blocking, and mountain waves) may also impact on the atmospheric circulation. Optimizing the parameterization schemes could be helpful for further improving the RWS simulation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Han et al, 2016;Van Weverberg et al, 2012) have shown that parameterization schemes on convection, subgrid-scale cloud microphysical process of the convective clouds and resultant precipitation all can affect the convergence/divergence in models. Recent study by Sandu et al (2019) suggests that parameterization schemes on topographic processes (e.g., turbulent form drag, low-level flow blocking, and mountain waves) may also impact on the atmospheric circulation. Optimizing the parameterization schemes could be helpful for further improving the RWS simulation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The drag imparted on the atmosphere by orography plays an important role in the momentum budget and, correspondingly, the atmospheric circulation. The representation of orographic drag in numerical models therefore influences the reliability of predictions across all time‐scales, from days (Sandu et al, ) to climate time‐scales (Pithan et al, ; van Niekerk et al, ). However, models used for numerical weather prediction (NWP), seasonal forecasting and climate projections typically only resolve a portion of the orographic scales, resulting in the need for orographic drag parametrisation schemes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the multiscale nature of orography and its impacts, orographic processes are only resolved in part by numerical models; processes occurring at scales smaller than the typical resolution of global climate (O(100 km)) or NWP models (O(10 km)) need to be parametrized. To date, the representation of unresolved orographic processes in numerical models remains a major challenge (Sandu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, if the orographic drag parametrizations would be perfect, they should account for unresolved orographic effects at all resolutions and the skill gained by increasing the orographic resolution should be negligible. In practice, however, parametrizations of orographic effects are known to be uncertain and poorly constrained (Sandu et al, , ; Zadra, ). They also behave inconsistently across resolutions, in the sense that they do not accurately account for the handover between resolved and parametrized orographic drag as the resolution is varied (Brown, ; van Niekerk et al, ; Vosper, ).…”
Section: Introductionmentioning
confidence: 99%